Penentuan Lokasi Lahan dengan Sistem Pendukung Keputusan Kriteria Jamak Berbasis Sistem Informasi Geografis - Herlawati, Herlawati; Khasanah, Fata Nidaul (Universitas Muhammadiyah Magelang, 2020)
Searching for appropriate land for a specific purpose is important, especially in a city. Some studies used multicriteria analysis searching for the best location, such as AHP, ANP, SAW, etc. However, the study usually uses some statistical methods that need more processing for the end-users. This study uses a Geographic Information System (GIS) to implement the multicriteria analysis for searching the proper land use location, especially for business and education in Bekasi City, West Java, Indonesia. Same layers for analysis were created using ArcGIS 10.1, including pollution, road, flood risk, open space/park, lake and recreation area, and land price. The weight-overlay method was used as a multicriteria method. The result showed the three regions for business and education, i.e. high, medium, and low suitability. The conversion from the region into administrative boundary is generated in order easy for local land-use planners to implement their plans.